CHLAMYDIA IN CATTLE REPRODUCTION - Maciaszek, Katarzyna (Translational Research in Veterinary Science, 2023)
Well-run reproduction, both in beef and dairy herds, determines the profitability of production. Knowledge of the factors affecting the reproduction of cattle allows you to undertake procedures to prevent or reduce their adverse impact. In addition, in the case of disease agents with zoonotic potential, knowledge about them determines the safety of personnel working with cattle on a daily basis – breeders, veterinarians. An example of such a factor is bacteria from the Chlamydiaceae family, gram-negative microorganisms found in many animal species as well as in humans. For cattle, the most pathogenic are C.abortus, C.pecorum and C.pistici. The disease has been known for a long time, but its role in cattle breeding is still underestimated. The results of monitoring studies conducted in different countries differ quite significantly from each other, and the obtained results indicate prevention from 0.4% through 4.44% up to 100% of the examined herds. Different species of Chlamydia cause different forms of disease. Chlamydia abortus is mainly associated with pathologies in the genital organs, abortions, embryonic death, metritis and mastitis. In addition to abortions, it can cause dead calves to be born at the right time or weak newborns that die within a few days for unspecified reasons. In the subclinical form, it may be responsible for lower fertility rates and high somatic cell counts. Epididymitis and alveolar gland inflammation may occur in bulls. Chlamydia pecorum, in turn, is more pathogenic for calves, causing inflammation of the intestines, brain and spinal cord, joints, lungs, cornea and conjunctiva, and kidneys. However, this division is not very rigid, as there are cases of obtaining positive results from vaginal swabs towards Ch. abortus of several-week-old calves. Ch. psittaci is extremely rare in cattle, but it can be responsible for abortions and pneumonia. Long-term antibiotic therapy with the use of tetracyclines, macrolides and fluoroquinolones brings some results in the form of alleviation of clinical signs associated with the presence of chlamydiosis in the herd. However, it does not reduce shedding and may lead to latent infections. In order to reduce the disease, the focus should be on maintaining an appropriate standard of hygiene and biosecurity. Separating infected animals, removing aborted fetuses and quarantining newly introduced animals are the basic elements of the fight against this disease entity. Unfortunately, there are no vaccines against chlamydia registered for cattle available on the Polish market. However, when using a pharmacological cascade, a preparation available for sheep, providing protection against Ch. abortion. The combination of vaccination, appropriate maintenance and hygiene conditions, and biosecurity make it possible to control chlamydiosis in dairy and beef cattle herds.